Pituitary Neuroendocrine Tumors in Multiple Endocrine Neoplasia - Sang Ouk Chin; Constance Chik; Toru Tateno (Endocrinology and Metabolism)
Multiple endocrine neoplasia type 1 (MEN1) is an autosomal-dominant disorder characterized by tumors of the pituitary, parathyroid, and endocrine-gastrointestinal tract. Pituitary neuroendocrine tumors (PitNETs) occur in about 40% of MEN1 cases, with 10% being the first manifestation. Recent studies show a slight female predominance, with microPitNETs (<1 cm) being more common than macroPitNETs (>1 cm). Functional PitNETs (FPitNETs) are more frequent than non-functional ones (36% to 48%), with prolactinomas being the most common FPitNETs. MEN1-associated PitNETs are often plurihormonal, larger, and more invasive compared to sporadic types, though patient age and FPitNET proportions are similar. MEN1 mutation-negative patients tend to have larger, symptomatic PitNETs at diagnosis. Six patients with MEN1 have been reported to have pituitary carcinomas, including a mutation-negative patient. Treatment approach between PitNETs in MEN1 and sporadic types appears to be similar. PitNETs also occur in MEN4, but their epidemiology is less understood. In patients with a MEN1-like phenotype and negative genetic testing, MEN4 should be considered.